Preparation method and application of porous carbon and sulfur composite material

Porous carbon materials are prepared based on pore-making auxiliary agents and combined with sulfur powder, which solves the problems of high preparation cost of porous carbon materials and poor performance of lithium sulfur batteries, and realizes the preparation of low-cost and high-performance porous carbon and sulfur composite materials, which is suitable for the positive electrode material of lithium sulfur batteries.

CN119833621APending Publication Date: 2025-04-15NANJING UNIV
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510142555.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-24
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing porous carbon material preparation methods have problems such as high preparation costs, complex processes, and environmental pollution, and it is difficult to achieve low-cost large-scale production. At the same time, the practical application of lithium-sulfur batteries is restricted by poor sulfur conductivity, large volume changes in the charging and discharge process, and the "shuttle effect" of polysulfides.

Method used

Porous carbon materials are prepared by a method based on pore-making auxiliary agent. By mixing the carbon source with the pore-making auxiliary agent and mechanically pressurized, and then pyrolyzed in an inert atmosphere, porous carbon materials with high specific surface area and graded pore structure are obtained, and composited with sulfur powder to form porous carbon and sulfur composite materials.

Benefits of technology

It realizes a low-cost, simple and environmentally friendly preparation process for porous carbon materials, with a high specific surface area and a hierarchical pore structure. As a self-supporting positive electrode carrier material for lithium sulfur batteries, it shows excellent specific capacity, cycle stability and high surface loading performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119833621A_ABST
    Figure CN119833621A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of a porous carbon / sulfur composite material, and belongs to the field of carbon material preparation. The preparation method comprises the following steps that firstly, a carbon source and a pore-forming auxiliary agent are ground and mixed, the carbon source is a biomass material, and the pore-forming auxiliary agent is zinc-based powder; then mechanically pressing the mixture to form a cast ingot, heating the cast ingot in a protective atmosphere, removing the thermally volatile pore-forming auxiliary agent through a heat preservation process, and cooling the cast ingot to room temperature to obtain a porous carbon material; and finally, preparing the porous carbon / sulfur composite material through a gas-phase sulfur loading process. The preparation process is simple, the cost is low, large-scale production is easy to realize, and the prepared porous carbon material has a high specific surface area and a hierarchical pore structure, can be used as a self-supporting positive electrode carrier of a lithium-sulfur battery, and provides a new technical path for development of the high-performance lithium-sulfur battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of carbon material preparation, and specifically relates to a method for preparing a porous carbon and sulfur composite material. Background Art

[0002] Porous carbon materials have great potential in the field of electrochemical energy storage due to their lightweight and porous structural characteristics and excellent electrical conductivity. The internally coherent solid-phase conductive network and interconnected pore network are conducive to electron conduction and ion transport, making them ideal electrode materials. Compared with traditional electrode materials, porous carbon electrodes do not require the use of non-electrochemically active binders, conductive agents and metal current collectors, which can significantly improve the energy density of electrochemical systems. However, the existing preparation methods of porous carbon materials mainly rely on template methods, which have problems such as high preparation cost, complex process and environmental pollution, which has become a key technical bottleneck restricting its large-scale application. Biomass, as a cheap, renewable and widely available carbon source, provides the possibility for low-cost large-scale preparation of porous carbon materials. However, direct pyrolysis of biomass usually only obtains dense solid carbon blocks, which is difficult to form a porous structure, and it is necessary to introduce suitable auxiliary agents to regulate the pyrolysis process. The development of solid-phase pyrolysis large-scale preparation technology based on biomass and renewable auxiliary agents is the key to achieving large-scale production of low-cost porous carbon materials.

[0003] With the rapid development of electric vehicles and portable electronic devices, the performance requirements for lithium-ion batteries are increasing. Sulfur cathode materials are considered to be one of the most promising next-generation cathode materials due to their high theoretical specific capacity and abundant natural resource reserves. However, the practical application of lithium-sulfur batteries is still restricted by the poor conductivity of sulfur, large volume changes during the charge and discharge process, and the "shuttle effect" of polysulfides. More importantly, increasing the surface loading of sulfur is a key technical problem in achieving high-energy-density lithium-sulfur batteries. Therefore, developing new sulfur cathode carrier materials and constructing efficient and stable composite cathode materials have become a top priority for achieving high-performance lithium-sulfur batteries. Porous carbon materials, with their unique three-dimensional network structure and excellent conductive properties, provide new ideas and technical approaches to solve the above problems. Summary of the invention

[0004] The present invention aims to solve the technical problems existing in the prior art, provide a method for preparing a porous carbon material based on a pore-forming auxiliary agent, and provide a porous carbon and sulfur composite material. The method has the characteristics of simple process, low cost, and suitability for large-scale production. The prepared porous carbon material has a high specific surface area and a hierarchical pore structure, and can be used as a self-supporting positive electrode carrier material for high-performance lithium-sulfur batteries, and has broad application prospects.

[0005] The technical solution adopted by the present invention comprises the following steps:

[0006] (1) weighing a carbon source and a pore-forming auxiliary agent according to a predetermined mass ratio, grinding and mixing them thoroughly to obtain a uniform powder mixture, and then mechanically pressing and molding to obtain an ingot with a specific geometric shape;

[0007] (2) placing the ingot obtained in step (1) in a reaction furnace, introducing an inert atmosphere as a protective gas, heating the temperature from room temperature to 1100° C. at a heating rate of 2° C. / min, keeping the temperature for 3 hours, and obtaining a porous carbon material after cooling.

[0008] (3) The porous carbon material and sulfur powder prepared above were placed in a sealed container according to a predetermined mass ratio, and then kept at 180° C. for 12 hours. After cooling, a porous carbon and sulfur composite material was obtained.

[0009] In a preferred embodiment of the present invention, the carbon source in step (1) is an organic carbon source derived from biomass such as rice husk, pulp, cellulose, etc., and the pore-forming auxiliary agent is zinc, zinc oxide or any combination thereof.

[0010] In a preferred embodiment of the present invention, the inert atmosphere in step (2) is any one of nitrogen, argon, and hydrogen, or a combination of more than one of them. Nitrogen is preferred in terms of cost.

[0011] In a preferred embodiment of the present invention, the temperature range of thermal volatilization to remove the pore-forming agent in step (2) is 950-1500° C., and the holding time is 0.5-10 hours.

[0012] In a preferred embodiment of the present invention, the temperature range of the gas-phase sulfur-carrying process in step (3) is 160 to 220° C., and the holding time is 6 to 12 hours.

[0013] Compared with the prior art, the present invention has the following significant advantages:

[0014] 1) The present invention adopts a simple and environmentally friendly process route with low equipment requirements. By using low-cost biomass-derived organic carbon sources and removing the zinc-based pore-forming agent by thermal volatilization, the traditional acid-washing step of removing the pore-forming agent is avoided, and the condensed and deposited zinc-based pore-forming agent can be recycled and reused, which greatly reduces the preparation cost and can achieve large-scale preparation of porous carbon materials.

[0015] 2) The mechanical pressurization process promotes sufficient contact between the organic carbon source and the pore-forming auxiliary agent, which is conducive to the construction of a three-dimensional cross-linked network structure and can flexibly control the macroscopic morphology of the porous carbon material to meet the needs of different application scenarios.

[0016] 3) The porous carbon material prepared by the present invention has high specific surface area and hierarchical pore structure characteristics, and constructs a coherent solid-phase conductive network and ion transport pore network. When used as a self-supporting positive electrode carrier material for lithium-sulfur batteries, no additional binder, conductive agent and current collector are required, and it exhibits excellent specific capacity, cycle stability and high surface loading performance. The lithium-sulfur battery assembled based on porous carbon and sulfur composite materials can achieve a specific capacity of 1337mAh / g at a rate of 0.2C, and a capacity retention rate of 71.4% after 500 cycles at a rate of 1C, and a capacity retention rate of 10.3mg / cm -2 After 60 cycles at a surface loading of 9.1 mAh / cm -2 . BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is an optical photograph of the macroscopic morphology of the porous carbon material prepared in Example 1 of the present invention.

[0018] Figure 2 The microstructure characterization results of the porous carbon material prepared in Example 1 of the present invention, wherein (a) is a scanning electron microscope photograph, and (b) is a transmission electron microscope photograph.

[0019] Figure 3 This is the X-ray diffraction spectrum of the porous carbon material prepared in Example 1 of the present invention.

[0020] Figure 4 This is a Raman spectrum of the porous carbon material prepared in Example 1 of the present invention.

[0021] Figure 5 This is the nitrogen adsorption-desorption curve of the porous carbon material prepared in Example 1 of the present invention.

[0022] Figure 6 When the porous carbon and sulfur composite material prepared in Example 1 of the present invention is used as the positive electrode of a lithium-sulfur battery, the first charge and discharge curve of the assembled lithium-sulfur battery at a rate of 0.2C.

[0023] Figure 7 When the porous carbon and sulfur composite material prepared in Example 1 of the present invention is used as the positive electrode of a lithium-sulfur battery, the capacity change curve of the assembled lithium-sulfur battery after 500 cycles at a 1C rate.

[0024] Figure 8 When the porous carbon and sulfur composite material prepared in Example 1 of the present invention is used as the positive electrode of a lithium-sulfur battery, the cycle performance of the assembled lithium-sulfur battery at a rate of 0.2C under different sulfur surface loading conditions. DETAILED DESCRIPTION

[0025] The present invention will be described in detail below with reference to the accompanying drawings and through specific embodiments, but the protection scope of the present invention is not limited to the following embodiments.

[0026] Embodiment 1:

[0027] (1) 3 g of rice husk powder and 30 g of zinc powder with a particle size of about 1 μm were mixed and ground to obtain a uniform mixed powder. A certain amount of the mixed powder was weighed and placed in a pressure mold. The mixture was pressed using a tablet press at a pressure of 20 MPa to obtain a cylindrical ingot. (2) The ingot was placed in a tubular furnace, and under the protection of a nitrogen atmosphere, the temperature was raised from room temperature to 1100°C at a rate of 2°C / min. After keeping the temperature for 3 hours, the mixture was naturally cooled to obtain a porous carbon material. (3) The porous carbon material and sulfur powder prepared above were separated according to a predetermined mass ratio and placed in a sealed container. The mixture was then kept at 180°C for 12 hours. After cooling, a porous carbon and sulfur composite material was obtained.

[0028] The porous carbon material obtained in Example 1 is presented as a black foam that can be clamped ( Figure 1 ), and its scanning electron microscope photo ( Figure 2 ) shows that the material has a coherent skeleton structure, with spherical holes of about 1 μm distributed on the surface; the black block sample was ground and then subjected to X-ray diffraction analysis ( Figure 3 ), whose characteristic peaks completely correspond to those of graphite, indicating that the material has high crystallinity and purity; Raman spectroscopy analysis ( Figure 4 ) shows that there are abundant defects on the surface of the material, and these defect sites are conducive to the adsorption and conversion of polysulfides; the nitrogen adsorption and desorption curve ( Figure 5 ) shows that the specific surface area of ​​the material reaches 1081m 2 / g and has a hierarchical porous structure, which is conducive to the effective loading of active sulfur.

[0029] The porous carbon and sulfur composite material prepared above was used as the positive electrode of lithium-sulfur battery, and the lithium-sulfur battery was assembled for performance testing. The results showed that it had excellent specific capacity ( Figure 6 ), cyclic stability ( Figure 7 ) and high surface loading performance ( Figure 8 ). Specifically, the first discharge capacity at 0.2C rate reached 1337mAh / g; the capacity retention rate after 500 cycles at 1C rate was 71.4%; at 10.3mg / cm -2 After 60 cycles at a surface loading of 1.5 mAh / cm, the surface capacity remained at 9.1 mAh / cm -2 .

[0030] Embodiment 2:

[0031] 3 g of rice husk powder in step (1) of Example 1 was replaced by 3.5 g of pulp powder, and the remaining operations were the same as those of Example 1. The obtained porous carbon material also presented macroscopic foam and had a three-dimensional cross-linked network structure, and its specific surface area and hierarchical pore structure were comparable to those of Example 1, and the lithium-sulfur battery performance was similar to that of Example 1.

[0032] Embodiment 3:

[0033] 3 g of rice husk powder in step (1) of Example 1 was replaced by 3 g of cellulose powder, and the remaining operations were the same as those of Example 1. The obtained porous carbon material had a macroscopic foam morphology and a three-dimensional cross-linked network structure similar to those of Example 1, and its specific surface area, hierarchical pore structure and lithium-sulfur battery performance were comparable to those of Example 1.

[0034] Embodiment 4:

[0035] The 30 g zinc powder with a particle size of about 1 μm in step (1) of Example 1 was replaced with 25 g zinc oxide powder with a particle size of about 1 μm, and the remaining operations were the same as those of Example 1. The obtained porous carbon material also presented a macroscopic foam shape and had a three-dimensional cross-linked network structure, and its specific surface area, hierarchical pore structure and lithium-sulfur battery performance were comparable to those of Example 1.

[0036] Embodiment 5:

[0037] The 30 g of zinc powder with a particle size of about 1 μm in step (1) of Example 1 was replaced with 40 g of zinc powder with a particle size of about 10 μm. The remaining operations were the same as in Example 1, and a porous carbon material was successfully prepared.

[0038] It should be noted that the present invention is not limited to the methods and materials described in the above specific embodiments, and those skilled in the art may make appropriate adjustments and modifications according to actual needs. The terms used herein are only used to describe specific embodiments and are not intended to limit the present invention. The scope of protection of the present invention is defined by the attached claims and their equivalents.

Claims

1. A method for preparing a porous carbon and sulfur composite material, characterized in that: The method comprises the following steps: (1) weighing a carbon source and a pore-forming auxiliary agent according to a predetermined mass ratio, grinding and mixing them thoroughly to obtain a uniform powder mixture, and then mechanically pressing and molding to obtain a block ingot with a specific geometric shape; (2) placing the block ingot obtained in step (1) in a reaction furnace, introducing an inert atmosphere as a protective gas, heating the temperature from room temperature to 1100° C. at a heating rate of 2° C. / min, keeping the temperature for 3 hours, and then cooling to obtain a porous carbon material; (3) The porous carbon prepared in step (2) and sulfur powder are placed in a sealed container according to a predetermined mass ratio, kept at 180° C. for 12 hours, and cooled to obtain a porous carbon / sulfur composite material.

2. The method for preparing a porous carbon and sulfur composite material according to claim 1, characterized in that: In the step (1), the carbon source is selected from organic carbon sources derived from biomass such as rice husk, pulp, cellulose, etc., and the pore-forming auxiliary agent is zinc, zinc oxide or any combination thereof.

3. The method for preparing a porous carbon and sulfur composite material according to claim 1, characterized in that: In step (2), the inert atmosphere is selected from one or more combinations of nitrogen, argon and hydrogen.

4. The method for preparing a porous carbon and sulfur composite material according to claim 1, characterized in that: The temperature range of thermal volatilization to remove the pore-forming agent in step (2) is 950-1500° C., and the insulation time is 0.5-10 hours.

5. The method for preparing a porous carbon and sulfur composite material according to claim 1, characterized in that: The temperature range of the gas phase sulfur carrying process in step (3) is 160 to 220° C., and the insulation time is 6 to 12 hours.

Citation Information

Patent Citations

  • Preparation methods of catkin biomass based porous carbon and carbon-sulfur composite material

    CN107689446A

  • Preparation and application of biomass carbon / sulfur composite material

    CN110176597A

  • Preparation method and application of biomass porous carbon material based on nutshells

    CN111333068A

  • Method for preparing three-dimensional graphene foam material

    CN111825078A

  • Preparation method of lithium-sulfur battery positive electrode material, positive electrode material and application

    CN115676821A